STRATEGI PROGRAM KOMERSIALISASI UNTUK FAKULTAS SENI DAN DESAIN FAKULTAS INDUSTRI KREATIF, UNIVERSITAS TELKOM - Rara Diasa Djajataruna; Muhammad Hisyam Alfarisi; Raditya Raihannaufal Rahardyan; Fajar Ciptandi (Jurnal Education and Development, 2023)
This research aims to make strategic recommendations to art and design faculties regarding commercial programs for additional funds for faculty development. This study employs Mix Method for data collection, which includes interviews, questionnaires, and observation. The population in the questionnaire was bachelor students from the Faculty of Creative Industries represented by a sample of 150 students from the 2019 and 2020 batches. Five heads of expertise groups, six heads of study programs, and three Deans of the Faculty of Art and Design from Comparative Universities were interviewed. The findings of interviews and questionnaires indicate subject of the study still has many deficiencies in terms of facility quality and variety, owing to a lack of incoming funds for the development and revitalization of related facilities. So, in order to design the best strategy, a strategy for raising more funds for faculty development is required. To identify industry opportunities, observations are made on research objects and competitors, which will serve as the foundation for future strategy designs. Based on the observations, it was determined that in order for the research object to receive additional funding, a commercial program, which is a national/international training or certification in art and design with project-based characteristics, should be developed.